The Concept of Death in Emily Dickinson Poem "Because I Could Not Stop for Death" - Samanik, Samanik - (SIGEH ELT : Journal of Literature and Linguistics, 2024)
Â When a poet writes a poem, it may be influenced by his / her feeling and situation. Similarly, based on Emily Dickinsonâ€™s biography, it is told that since 1874 she spent her life in mourning because of several deaths. Emily's father died in 1874, Samuel Bowles died in 1878, J.G. Holland died in 1881, her nephew Gilbert died in 1883, and both Charles Wadsworth and Emily's mother died in 1882. For over those few years, many of the most influential and precious friendships of Emily's passed away (http://www.edwardslys.com/dickinson.htm). The situation that happened to her absolutely influenced her feeling. Then, it may give her a way to the more concentrated obsession with death in her poetry. This study shows influence of Emily Dickinsonâ€™s life background on the concept of death found in her poem â€œBecause I Could Not Stop for Deathâ€. The poem is influenced by the poetâ€™s life background as follows;Â  Her religious background includes Calvinism, Puritanism and Transcendentalism give influence to her perception of death.Â